Maintenance Contract versus Maintenance Donation in Romanian Legislation - Bancila, Daniel (Acta Universitatis Danubius. Juridica, 2022)
The present research aims at the analysis and comparison of the maintenance contract with the donation contract with the task of maintenance in the Romanian legislative regulation. Starting from the definition of notions, we will identify and list the legal effects and the characters of each type of contract among those analyzed, we will delimit from other contracts. The need to compare the two contracts is of particular importance, because we bring up the issue of the legal mortgage of the maintenance creditor compared to the burden of maintenance in the donation contract which ultimately represents a modality of the legal act. As for the maintenance creditor, it is protected by the legislator with a real claim guaranteed by a mortgage right on the alienated property, while in the case of donations with the charge, this charge is noted in the land book having the effect of obedience to third parties, if the liberality has as object rights subject to publicity formalities, the task must comply with the same formalities. In the case of real estate, the task is subject to notation in the land book.